Joint Discriminative Sparse Coding for Robust Hand-Based Multimodal Recognition - Li, Shuyi; Zhang, Bob (IEEE transactions on information forensics and security, 2021)
Multimodal biometrics recognition has recently attracted much interest for its higher security and effectiveness compared with unimodal biometrics recognition. However, most of the conventional multimodal recognition approaches generally focus on extracting semantic information from different modalities independently, while ignoring the implicit correlations among inter-modality. In this paper, we propose a simple yet effective supervised multimodal feature learning method, called joint discriminative sparse coding (JDSC), which is applied for hand-based multimodal recognition including finger-vein and finger-knuckle-print fusion, palm-vein and palmprint fusion, as well as palm-vein and dorsal-hand-vein fusion. Considering that relevant samples from different modalities have semantic correlations, JDSC projects the raw data into a shared space in which the distance of the between-class is maximized and the distance of the within-class is minimized, at the same time, the correlation among the inter-modality of the within-class is maximized. Therefore, sparse binary codes quantified by the obtained projection matrix can have more discriminative power for multimodal recognition tasks. Thorough experiments on six commonly used multimodal datasets demonstrate the superiority of our proposed method over several state-of-the-art techniques.